Dissociation of Retinal Ganglion Cells Without Enzymes - Hayashida, Yuki (2004)
We describe here methods for dissociating retinal ganglion cells from adult goldfish and rat without proteolytic enzymes, and show responses of ganglion cells isolated this way to step-wise voltage changes and fluctuating current injections. Taking advantage of the laminar organization of vertebrate retinas, photoreceptors and other cells were lifted away from the distal side of freshly isolated goldfish retinas, after contact with pieces of membrane filter. Likewise, cells were sliced away from the distal side of freshly isolated rat retinas, after these adhered to a membrane filter. The remaining portions of retina were incubated in an enzyme-free, low Ca(2+) solution, and triturated. After aliquots of the resulting cell suspension were plated, ganglion cells could be identified by dye retrogradely transported via the optic nerve. These cells showed no obvious morphological degeneration for several days of culture. Perforated-patch whole-cell recordings showed that the goldfish ganglion cells spike tonically in response to depolarizing constant current injections, that these spikes are temporally precise in response to fluctuating current injections, and that the largest voltage-gated Na(+) currents of these cells were larger than those of ganglion cells isolated with a neutral protease.